2020
DOI: 10.1021/acs.jafc.0c04723
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Metabolome Analysis Reveals the Metabolic Fate of Medium-Chain Fatty Acids in AML12 Cells

Abstract: Several studies in hepatocyte cell lines reported that medium-chain fatty acids (MCFAs) with 6–12 carbons showed different metabolic properties from long-chain fatty acids (LCFAs). However, these studies reported unclear effects of different fatty acid molecules on hepatocyte metabolism. This study is aimed to capture the metabolic kinetics of MCFA assimilation in AML12 cells treated with octanoic acid (FA 8:0), decanoic acid (FA 10:0), or lauric acid (FA12:0) [LCFA; oleic acid (FA 18:1)] via metabolic profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…organic acids, nucleotides, etc.) [ 70 , 71 ] and a liquid chromatography with a Discovery HS F5 column (2.1 mm i.d. 150 mm, 3 µm particle size, Merck, Darmstadt, Germany) coupled with a quadrupole-Orbitrap mass spectrometry (PFPP-LC/MS) (Thermo Fisher Scientific) for cationic polar metabolites (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…organic acids, nucleotides, etc.) [ 70 , 71 ] and a liquid chromatography with a Discovery HS F5 column (2.1 mm i.d. 150 mm, 3 µm particle size, Merck, Darmstadt, Germany) coupled with a quadrupole-Orbitrap mass spectrometry (PFPP-LC/MS) (Thermo Fisher Scientific) for cationic polar metabolites (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…amino acids, etc.) [ 70 , 71 ]. After the aqueous layer extracts were evaporated under vacuum, dried extracts were stored at −80°C until use for IC/MS and PFPP-LC/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…4 ). A previous report showed that ketone bodies were rapidly released from hepatocytes and were detected in the culture medium in vitro [ 15 ]. In fact, β-hydroxybutyrate in the gastrocnemius and plasma was significantly enhanced and remained high throughout the experiment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Three liquid chromatography mass spectrometry methods for metabolome analysis were employed as described previously [ 15 , 16 ]. Anionic polar metabolites (i.e., citrate, cis -aconitate, isocitrate, α-ketoglutarate, succinate, malate, fumarate, glucose) were analyzed using ion chromatography (Dionex ICS-5000 + HPIC system, Thermo Fisher Scientific, Waltham, MA, USA) with a Dionex IonPac AS11-HC-4 μm column (2 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, in the SFC/MS method (Method E), all lipid molecules in the same class were eluted at similar retention times by SFC-based lipid class separation [28]. Because this technique (Method E) co-elutes the same class of lipids, the ion-suppression and/or ion-enhancement effects of the biological matrix can be normalized by adding the appropriate internal standards of each lipid class (stable isotope-labeled lipid standards) [19,28]. However, in this study, to clarify the cause of the inconsistency in the relative quantification (S-1/S-3) results from the analytical methods, the relative quantification values were calculated using the raw data (peak area or height) without correcting the acquired data with the internal standards.…”
Section: Hydrophobic Metabolitesmentioning
confidence: 99%